Implementasi Pendidikan Karakter di Sekolah Menengah Pertama (SMP) dan Sekolah Menengah Atas (SMA) Al-Wildan melalui Program Overseas di Universitas Islam Madinah - Al-Basyir, Muhammad (Rayah Al-Islam, 2026)
The implementation of character education at Al-Wildan Junior High School and Al-Wildan Senior High School through an overseas program at the Islamic University of Madinah is designed to comprehensively internalize Islamic character values among students. This program integrates religious instruction with international educational experiences to foster students’ moral integrity, independence, and global competitiveness. This study adopts a qualitative research design. Data were collected through interviews, classroom observations, and document analysis, involving teachers and students from Al-Wildan Junior and Senior High Schools. The data were analyzed descriptively through three stages: data reduction, data presentation, and conclusion drawing. The findings indicate that the program effectively integrates academic learning with character development within a supportive educational environment, resulting in significant positive changes in students. These improvements are evident across several dimensions, including Arabic language proficiency, diniyah studies and Qur’anic competence, worship practices and moral conduct, as well as independence and learning motivation. Overall, the program contributes to enhancing students’ quality and capacity and is expected to produce graduates with strong character who are well prepared to face global challenges.